Natural history of hepatic hemangioma: a follow-up analysis of 534 patients. Issue 1 (1st January 2019) - Wang, Ankang; Deng, Jiaqi; Qian, Baolin; Chen, Hao; Li, Mingxing; Yang, Dayin; Li, Qiu; Lei, Zhengming; Fu, Wenguang
Abstract : Background: The effects of gender and age on the growth of hepatic hemangioma remain inconclusive. This study aims to further explore the natural growth of hepatic hemangioma and its influencing factors. Methods: From June 2014 to April 2019, 534 untreated patients who were diagnosed with hepatic hemangioma in our hospital were enrolled. The growth changes of hepatic hemangioma were observed at follow-up by ultrasound. Results: During the median 18 (14, 22) (months of follow-up, 215 (40.3%) patients showed an increase in tumor diameter, 217 (40.6%) tumor diameters decreased, and102 (19.1%) tumor diameters did not change. Before the age of 40, the diameter of hemangiomas in each group of men and women increased with age. After 40 years old, those in men continued to grow slowly, while those in women had a relatively downward trend. Therefore, by investigating annual changes in tumor, it was found that the diameter of female tumors showed a significant downward trend after the age of 40, the difference is most pronounced between 50–60 years old (the annual change is −0.39 (−0.87, 0.40) cm). Conclusion: In the natural growth process of hepatic hemangioma, male and female patients present different trends, which may be related to sex.